The Modification of Plinko Game to Learn Speaking for College Students - Isnaini Nurhaya; Arita Destianingsih (LPPM Universitas Bumigora Mataram, 2021)
The purpose of this study was modifying a game as a media in teaching and learning to encourage university students in learning English especially speaking skills. The game was plinko game. In this study, the game was called plinko speaking game. A plinko speaking game was a game which used board, balls and task cards as media to play this game. This study belongs to descriptive method, which was aimed to describe the processes and the rule to play this game. Descriptive research “Is designed to provide a picture of a situation as it naturally happens”. It may be used to justify current practice and make judgment and also to develop theories. In designing the product, there were several ways that in designing the product; first, preparing the equipment and the material, preparing material of the topic cards’ theme, designing the board, designing the card, printing the cards, designing the ways how to play the game, doing the evaluation the product at university, and finishing the product design. The result of this study is a set of A Plinko Speaking Game that consists of a board game, 50 task cards and 10 balls of plinko speaking game.